Imaging of placental vasculature using three-dimensional ultrasound and color power Doppler: a preliminary study - Dolores H. Pretorius; Thomas R. Nelson; Rebecca N. Baergen; E.F. Pai; Cathy J. Cantrell (1998)
Abstract Objective To assess placental vasculature using color power Doppler and three‐dimensional ultrasound techniques. Design A prospective study was performed in patients to correlate visualization of placental vessels in vivo with known anatomy. Subjects Fourteen normal patients and one patient with intrauterine growth restriction were recruited to the study. Methods Vessels were assessed with regard to, first, the number of vessels seen within the placenta, second, the branching pattern of the vessels within the placenta, third, the number of vessels seen along the surface of the placenta, and, last, the number of vessels seen in the maternal circulation. Results Our results show that the placental vessels seen with this technique correlate well with known anatomy. A progressive increase in the number of intraplacental vessels and the number of vascular branches observed was seen with increasing gestational age. Volume data review using three orthogonal planar images had two distinct advantages. First, they could be obtained from orientations not possible using two‐dimensional ultrasound alone, and, second, they could be viewed in conjunction with volume‐rendered images to allow for referencing and identification of specific vessels. Volume‐rendered images were valuable in allowing the observer to acquire an improved overall understanding of placental anatomy. They also assisted the observer in following the continuity of vessels as they wrapped around and twisted through three‐dimensional space. Stereo viewing was helpful in distinguishing overlapping vessels. Conclusions Our study showed that sonographic volume imaging combined with color power Doppler imaging methods allowed for individual vessels in the placenta to be identified, both in the fetal and maternal circulations. Copyright © 1998 International Society of Ultrasound in Obstetrics and Gynecology